2000
DOI: 10.1016/s0194-5998(00)70190-2
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and Long‐Term Outcomes of Canalith Repositioning for Benign Paroxysmal Positional Vertigo

Abstract: This is a prospective, nonrandomized study of the canalith repositioning procedure (CRP) for treatment of benign paroxysmal positional vertigo (BPPV). CRP was used to treat 168 patients with BPPV. Patient data were gathered by yearly telephone interviews to determine whether symptoms of position-induced vertigo had returned. After 1 or 2 treatment sessions 91.3% of patients reported complete symptom resolution. Average follow-up for the study population after the initial treatment was 26 months. A recurrence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
134
6
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(148 citation statements)
references
References 18 publications
7
134
6
1
Order By: Relevance
“…13 18 Benign paroxysmal positional vertigo is a recurring disease, with a recurrence rate of approximately 15% per year. 19 We found recurrence of BPPV in 56% of individuals, which is similar to values of 50% 20 and 55% 21 reported in other studies. One limitation of our study was that the follow-up time since the first manifestation of BPPV was less than 1 year in 25% of individuals.…”
Section: Clinical Manifestationsupporting
confidence: 91%
“…13 18 Benign paroxysmal positional vertigo is a recurring disease, with a recurrence rate of approximately 15% per year. 19 We found recurrence of BPPV in 56% of individuals, which is similar to values of 50% 20 and 55% 21 reported in other studies. One limitation of our study was that the follow-up time since the first manifestation of BPPV was less than 1 year in 25% of individuals.…”
Section: Clinical Manifestationsupporting
confidence: 91%
“…These include sleeping upright for 2 days, for further 5 days not to sleep on the affected side, and the use of soft collar. 3- 7 14 17 19 20 No statistically significant difference was found in the success rate, in two group of pts with and without post-treatment instructions. The authors concluded that post-treatment instructions were not beneficial for the management of BPPV and may be quite inconvenient and at times difficult to comply with.…”
Section: Discussionmentioning
confidence: 78%
“…Different procedures are recommended for increasing treatment success and decreasing recurrence of BPPV. These include using mastoid vibration when performing the canalith repositioning maneuver, having patients remain in a head-upright position for 48 h after repositioning to prevent loose debris from assuming a dependent position in the posterior canal, using a cervical collar after repositioning, avoiding sleep over the affected ear for at least 1 week, and performing repeat maneuvers during a BPPV episode [5,8,10].…”
Section: Discussionmentioning
confidence: 99%
“…Helminski and colleagues reported that 44% of patients who were treated successfully with the canalith repositioning procedure redeveloped BPPV within the first 2 years [11]. While Lopez-Escamez and colleagues found recurrence in 10% of patients with PC-BPPV after 1 year of follow-up, Nunez et al reported that the percent recurrence per year was approximately 15%, with approximately 50% having a recurrence by 40 months [10,12]. Rashad described recurrence in 7% of patients after 1 year, and after 5 years this increased to 35% [13].…”
Section: Discussionmentioning
confidence: 99%